Evaluation of the MeltPro TB/STR assay for rapid detection of streptomycin resistance in Mycobacterium tuberculosis. Issue 2 (March 2015) - Zhang, Ting; Hu, Siyu; Li, Guoli; Li, Hui; Liu, Xiaoli; Niu, Jianjun; Wang, Feng; Wen, Huixin; Xu, Ye; Li, Qingge
Summary Rapid and comprehensive detection of drug-resistance is essential for the control of tuberculosis, which has facilitated the development of molecular assays for the detection of drug-resistant mutations in Mycobacterium tuberculosis. We hereby assessed the analytical and clinical performance of an assay for streptomycin-resistant mutations. MeltPro TB/STR is a closed-tube, dual-color, melting curve analysis-based, real-time PCR test designed to detect 15 streptomycin-resistant mutations in rpsL 43, rpsL 88, rrs 513, rrs 514, rrs 517, and rrs 905–908 of M. tuberculosis. Analytical studies showed that the accuracy was 100%, the limit of detection was 50–500 bacilli per reaction, the reproducibility in the form of Tm variation was within 1.0 °C, and we could detect 20% STR resistance in mixed bacterial samples. The cross-platform study demonstrated that the assay could be performed on six models of real-time PCR instruments. A multicenter clinical study was conducted using 1056 clinical isolates, which were collected from three geographically different healthcare units, including 709 STR-susceptible and 347 STR-resistant isolates characterized on Löwenstein–Jensen solid medium by traditional drug susceptibility testing. The results showed that the clinical sensitivity and specificity of the MeltPro TB/STR was 88.8% and 95.8%, respectively. Sequencing analysis confirmed the accuracy of the mutation types. Among all the 8 mutation types detected, rpsL K43R (AAG → AGG), rpsL K88R (AAG → AGG) and rrs 514 A → C accounted for more than 90%. We concluded that MeltPro TB/STR represents a rapid and reliable assay for the detection of STR resistance in clinical isolates.